2003
DOI: 10.3358/shokueishi.44.186
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Detection of Staphylococcal Enterotoxin A Gene in Low Fat Milk Which Caused a Serious Outbreak of Food Poisoning

Abstract: In June 2000, there was a large-scale outbreak of food poisoning after consumption of Snow Brand low fat milk. In the evening of a day the incident made public, some cartons of low fat milk were brought to our laboratory for examination. Next day, we detected only staphylococcal enterotoxin (SE) A gene among SE (AῐE) genes by PCR in left-over milk samples or samples from the same lots that patients had consumed. We presumed that the outbreak was caused by the intake of SEA. We subsequently confirmed the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Intoxication by Staph. aureus is most frequently identified as the cause of human outbreaks resulting from raw milk consumption or products made thereof (Yamashita et al, 2003;Barker and Gomez-Tome, 2013;Claeys et al, 2013;Janstova et al, 2014). By contrast, with commercially processed milk, consumer health is potentially at risk from Staph.…”
Section: Short Communicationmentioning
confidence: 99%
“…Intoxication by Staph. aureus is most frequently identified as the cause of human outbreaks resulting from raw milk consumption or products made thereof (Yamashita et al, 2003;Barker and Gomez-Tome, 2013;Claeys et al, 2013;Janstova et al, 2014). By contrast, with commercially processed milk, consumer health is potentially at risk from Staph.…”
Section: Short Communicationmentioning
confidence: 99%
“…However, milk powder is easily contaminated with S. aureus (Wang et al, 2012). Although pasteurization can kill S. aureus cells, enterotoxins produced by S. aureus can still cause foodborne diseases in humans (Yamashita et al, 2003). In addition, studies have reported that some S. aureus strains persist in powdered infant formula (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These results disagreed with Shin et al, (2002) recorded that most Staph. aureus strains produced enterotoxin B and D.Also Yamashita et al, (2003) detected only Staphylococcal enterotoxin sea gene among se (a-e) genes by PCR in milk samples. Also Lim et al, (2004) detected SEA in 32 isolates, SEB in 3 isolates, SEC in 1 isolate and SEA in 1 isolates.…”
Section: Discussionmentioning
confidence: 89%